The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1088/0004-637x/782/1/53
|View full text |Cite
|
Sign up to set email alerts
|

THENUVrVERSUSMrPLANE AS A TRACER OF EARLY-TYPE GALAXY EVOLUTION IN THE USGC U376 AND LGG 225 GROUPS

Abstract: With the aim of tracing back the evolution of galaxies in nearby groups we use smooth particle hydrodynamical (SPH) simulations with chemo-photometric implementation. Here we focus on the evolution of the early-type members (Es and S0s, ETGs hereafter) in two groups, USGC U376 and LGG 225, both in the Leo cloud. We use the near-UV (NUV)-optical rest-frame (NUV − r) versus M r color magnitude diagram to follow their evolution, from the blue cloud (BC) to the red sequence (RS), through the green valley (GV). ETG… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 70 publications
1
36
0
Order By: Relevance
“…with 2 NUV−r 4, some of them very near to the blue sequence. This behaviour agrees with the findings of Mazzei et al (2014). These authors, studying the evolution of ETGs in two groups of the Leo cloud, USCG U376 and LGG 225, found that rejuvenation episodes are more frequent in fainter ETGs (see their Fig.…”
Section: The Uv -Optical Cmdsupporting
confidence: 90%
See 1 more Smart Citation
“…with 2 NUV−r 4, some of them very near to the blue sequence. This behaviour agrees with the findings of Mazzei et al (2014). These authors, studying the evolution of ETGs in two groups of the Leo cloud, USCG U376 and LGG 225, found that rejuvenation episodes are more frequent in fainter ETGs (see their Fig.…”
Section: The Uv -Optical Cmdsupporting
confidence: 90%
“…Our UV-optical analysis suggests that star formation events are still occurring in this group, in particular in its dwarf ETG population, tracing a picture of a still active phase notwithstanding its large number of ETGs and its likely virialized configuration (Table 2). Mazzei et al (2014), investigating the evolution of the brightest ETGs in the U376 and LGG 225 groups, found that residual star formation, i.e. "rejuvenation", is luminosity dependent so that bursts of star formation can occur still today in dEs, as found in this group.…”
Section: Discussionmentioning
confidence: 67%
“…The NUV−r color is an excellent tracer of even small amounts of SF (e.g. Mazzei et al 2014a). The first three panels of Fig.4 and Fig.5, from top to bottom, show the gas accretion history, the SFR and the mass assembly history derived within a fixed reference radius of 50 kpc, centered on the B-band luminous center of the galaxy.…”
Section: Resultsmentioning
confidence: 99%
“…Each simulation in the grid self-consistently provides morphological, dynamic, and chemo-photometric evolution. We applied already the same approach to ETGs belonging to the groups USGC 367 and LGG 225 (Mazzei et al 2014a), and to two S0 galaxies, namely NGC 3626 and NGC 1533, in Mazzei et al (2014b), where we match photometric, structural (e.g. disk vs. bulge) and kinematical (gas vs. stars) properties, showing that a major merger (1:1) accounts for the structural and photometric transformations expected in these systems (Querejeta et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…However, not all lenticulars live in clusters; today we know that probably at least half of the S0 population is located in the less dense environment of groups [13,14], where ram pressure is negligible, and mergers become increasingly relevant [15,16]. The aim of the talk given in the context of the European Week of Astronomy (EWASS) in Tenerife, June 2015, was to show how major mergers can transform spiral galaxies into lenticulars, in agreement with the tight photometric relations observed for S0s [5], and explaining the change in concentration and angular momentum found by CALIFA (van de Ven et al in preparation).…”
Section: Introductionmentioning
confidence: 99%